Trichinella nativa and Trichinella T6 in arctic foxes (Vulpes lagopus) from northern Canada. (December 2020) - Owsiacki, Robin; Buhler, Kayla J.; Sharma, Rajnish; Branigan, Marsha; Fenton, Heather; Tomaselli, Matilde; Kafle, Pratap; Lobanov, Vladislav A.; Bouchard, Émilie; Jenkins, Emily
Abstract: Parasitic zoonotic nematodes of the genus Trichinella circulate in wildlife and domestic hosts worldwide through the ingestion of infected meat. Due to their role as scavengers and predators in terrestrial and marine arctic ecosystems, Arctic foxes ( Vulpes lagopus ) are ideal sentinels for the detection of Trichinella spp. In this study, we determined the prevalence, larval intensity, and species of Trichinella from 91 trapped Arctic foxes collected around the northern Canadian communities of Sachs Harbour (Ikaahuk) on Banks Island (n = 23), and Ulukhaktok and Cambridge Bay (Ikaluktutiak) on Victoria Island (n = 68). Using pepsin-HCl digestion, larvae of Trichinella spp. were recovered from the left forelimb muscle ( flexor carpi ulnaris ) in 19 of the 91 foxes (21% prevalence, 95% CI: 14–30%). For the first time in Arctic foxes in Canada, Trichinella species were identified using multiplex PCR that was followed up with PCR-RFLP to distinguish between T. nativa and T. chanchalensis . All infected foxes harbored T. nativa, and one fox was co-infected with Trichinella T6; the latter is a new host record. Age of the fox was significantly associated with Trichinella spp. infection and the odds of being infected were three times higher in foxes ≥2 years of age (p = 0.026), indicating cumulative exposure with age. While Arctic foxes are seldom harvested for human consumption, they serve as sentinel hosts of Trichinella spp., confirming the presence of the parasite in wildlife in the region. Graphical abstract: Image 1 Highlights: Arctic foxes can serve as sentinel species for food-borne parasites like Trichinella. This study is the first to identify Trichinella T6 in Canadian Arctic foxes. The prevalence of Trichinella spp. in Arctic foxes was higher than previously reported. Adult foxes were three times more likely to be infected with Trichinella spp. than young foxes.